Aesthetics and Symbolic Meaning of Androgynous and CO-ED Style Trends in Men’s Fashion - Githapradana, Dewa Made Weda (Bina Nusantara University, 2022)
The research aimed to understand the aesthetic value and symbolic meaning of the co-ed and androgynous trends in men’s fashion. The problem discussed was how the aesthetic value and symbolic meaning of co-ed androgynous trends were in men’s fashion today. Co-ed and androgyny were one of the phenomena in men’s fashion trends today. The co-ed androgynous style featured a gender-fluid fashion concept; that was, the blurring of the binary gender opposition boundaries. Gender discrimination is a phenomenon of social problems that often surfaced. Fashion was often used as an instrument in reproducing gender identity in social systems. The development of men’s fashion had undergone significant changes in recent decades. Men’s clothing trends had become more attractive, dynamic, and no longer monotonous like conventional men’s fashion styles. The research applied a qualitative research method by collecting library data, observation, and interviews with practitioners and experts. The approach and theoretical basis used in analyzing the objects and variables were postmodern aesthetic approaches and Barthes’ semiotic theory. The object sample was the clothing designed by Alesandro Michele for the Gucci brand. The result indicates that the symbolic meanings of androgynous and co-ed trends are able to reflect social problems, such as reproducing gender identity, overhauling heteronormative stereotypes, changing gender roles, and freedom of expression without discrimination. The concept is expressed through a dynamic and free postmodern aesthetic.